Control interno del departamento de ventas y cobranza y su impacto en la rentabilidad en la empresa Quevecredicar S.A. del cantón Quevedo, provincia - Los Ríos, año 2021. - Torres Cedeño, Sandra Annabel (2023)
The current research work was carried out at the company Quevecredicar S.A. which is located in Quevedo canton. It aimed to evaluate the internal control and its impact on profitability to propose a manual of policies and procedures in the sales and collection department. Qualitative and quantitative research was used. This research was implemented for data collection; the tool model COSO I was also used for the application of an internal control questionnaire in order to collect information about the 5 components. The results showed deficiencies that do not allow the company Quevecredicar S.A. to have an adequate control in its procedures. In addition, the company does not have a manual of policies and procedures for the development of its daily activities; another fact is the lack of training, and the shortage of mission and vision. According to this, the results presented a confidence level of 74% as moderate level, while the level of control risk of 13% as low level and an inherent risk of 26% as moderate level. The consequence indicates that the company must continue working to improve the value of trust and risk inside the company by taking into account each aspect. According to the impact on profitability, the profitability indicators were applied, so obtaining that the gross margin is 96%; the margin has been maintained from 2020 to 2021 which indicates that a considerable profitability is being obtained in sales. Regarding the net margin during 2020 and 2021, a 0.73 and 0.65; it demonstrates that the company has been more profitable in 2020. Liquidity could be appreciated in 2020, 2021 with 18% and 13% respectively. It is evident that in 2020 the company had more liquidity than in 2021. A manual of policies and procedures was established for the sales and collection department to contribute to the improvement of the development of its activities.